2007
DOI: 10.1002/ejlt.200600307
|View full text |Cite
|
Sign up to set email alerts
|

Palm oil refining

Abstract: Crude palm oil is rich in minor components that impart unique nutritional properties. The most relevant are tocopherols and tocotrienols (vitamin E) and carotenoids (a-and b-carotene). Palm oil is generally refined by the physical process, which is preferred over the chemical process since high acidity (up to 5%) can lead to excessive loss of neutral oil in the soapstock after alkali neutralization. The quality of the crude oil is to be considered as it can greatly affect the efficiency of the refining process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
112
0
21

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 166 publications
(138 citation statements)
references
References 23 publications
5
112
0
21
Order By: Relevance
“…Their practice of storing palm fruits for between two and four weeks before processing leads to CPO with a high free fatty acid (FFA) content. This is not utilised by the refining industry because removal of FFAs incurs high oil losses and costs (Gibon et al, 2007). As a result, the country imports large quantities of CPO for industrial production of refined cooking oil, high value cosmetics and luxury soaps.…”
Section: The Case: Ghana's Oil Palm Domainmentioning
confidence: 99%
“…Their practice of storing palm fruits for between two and four weeks before processing leads to CPO with a high free fatty acid (FFA) content. This is not utilised by the refining industry because removal of FFAs incurs high oil losses and costs (Gibon et al, 2007). As a result, the country imports large quantities of CPO for industrial production of refined cooking oil, high value cosmetics and luxury soaps.…”
Section: The Case: Ghana's Oil Palm Domainmentioning
confidence: 99%
“…In conventional alkaline neutralization [2,4], the soapstock and neutralized oil mixture are separated in a centrifugal separator. The discharged oil contains 500-1000 ppm of soap.…”
Section: Process Potentialsmentioning
confidence: 99%
“…The non triglyceride materials in crude palm oil (CPO) consist of free fatty acids (FFA), partial acylglycerols, phospatides, glycolipids, tocopherols, tocotrienols, carotenoids, sterols, methylsterols, triterpene, isoprenoid alcohols, and hydrocarbons [2]. These components are valuable and their recovery from the oil also increases the quality of the oil in terms of color, taste, odor and stability.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…According to Gibon et al [2] crude palm oil (CPO), which is rich in minor components, has high value nutrients, such as tocopherol and tocotrienol (vitamin E), as well as carotenoid (α and β-carotene). Meanwhile, Nuzul Amri et al [3] reported that the properties of crude palm kernel oil (CPKO) are unchanged over the last 17 years based on a survey carried out for a year.…”
Section: Introductionmentioning
confidence: 99%